Technology Integration in Physical Education Curriculum Implementation in the Philippines: A Scoping Review - Tolentino, Julius Ceazar G.; Campo, Jaslee C.; Licup, Tristan O.; Lumba, Edison G.; Lingat, Erika G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The approach utilized in the study is a scoping review typically employed to map existing literature on a specific topic that undergoes an in-depth analysis, focusing on concepts, gaps, and findings. This study aimed to examine the technologies integrated into PE curriculum implementation and their benefits and challenges in the educational process in the Philippines. Moreover, in the methodological process, the Preferred Reporting Items for Systematic Reviews and Meta-Analyses for Scoping Reviews (PRISMA-ScR) framework are used to ensure the transparency and trustworthiness of the study. Three overarching themes were identified with the in-depth analysis of the literature selected. The first theme emphasized technology utilization in curriculum implementation in PE, which emphasizes integrated technologies and online education platforms. The second theme highlighted the benefits of technological integration in PE curriculum implementation, which has seen online learning and platforms as effective tools. Literature has stated that teachers, families, and the environment greatly impact the new learning modality. The third theme covered the challenges of technological integration in PE curriculum implementation, together with the resource and environmental challenges in online education. This also concerned components impacting teachers' and students' holistic development. Furthermore, this study found that from 2020 to 2024, online learning became a tool for continuous learning as an alternative to the COVID-19 pandemic. Institutions utilized various technologies for PE to support the curriculum implementation, as some foresaw the time as a learning experience and gained new skills, while others faced hindrances and challenges in these times.